The impact of structural capital in achieving the outstanding performance of ‎organizations: A field study in the industrial area in Msila - Hachemi Benouadah; Abdelmoutalib Bisar (Dirassat Journal Economic Issue, 2018)
This study is designed to attempt to highlight the impact of structural capital in achieving good performance of business organizations, where the search field study in the industrial area in the tear, to achieve this in practice according to the scientific methodology, the collection, processing and analysis are (53) a factor of five administrative staff located in the industrial area of Msila economic institutions, and the collection of data through the application form has been designed as a tool to measure the model of the study, the study used Descriptive and Inferential statistical methods to test to infuse more clarity, the most prominent of the findings of the study that there is an interest in the structural capital as well as the outstanding performance of institutions in the study, there are also linked to the impact of the strong positive link with statistical significance between structural capital and achieve outstanding performance, which reveal to us the effects of structural capital extensions in each The activities of the institutions.